Elementary Chinese II - Zhou, Wenying (Open textbook library., 2022)
Elementary Chinese II is aimed at those who have learned Chinese as a second/foreign language for one semester, using the OER textbook “Elementary Chinese I“. This open textbook contains six main lessons, including topics such as school life, shopping, transportation, weather, eating out, and asking and giving directions. They are organized in a straightforward and well-structured manner that are easy to follow. Within each lesson, there are a set of two dialogues or a set of one dialogue plus one narration. The texts of the dialogues or narrations are created to provide real-life Chinese language to beginning learners. After the texts, vocabulary words are listed for them to study and review. Grammatical points are explained in English and example sentences are provided for students to understand. Each dialogue or narration ends with culture notes where learners can read and better understand the target text.